ANALISIS YURIDIS JERATAN PIDANA TERHADAP PELAKU LESBIAN GAY BISEKSUAL TRANSGENDER DALAM UNDANG-UNDANG DI INDONESIA (TINJAUAN HUKUM PIDANA MILITER DAN HUKUM ADMINISTRASI PRAJURIT) - simanjuntak, mangisi (Fakultas Hukum Universitas Kristen Indonesia, 2024)
LGBT acts are difficult for most people to accept, but along with the development of the era, LGBT groups are increasingly widespread even in Indonesia. Of course, it requires special attention in the field of law related to the existence of the group, therefore it is necessary to have legal regulations related to LGBT acts as an act or as a criminal act, taking into account that the law in Indonesia uphold Customary Law based on legal norms in the community. Regulations related to LGBT acts have not been specifically regulated by legislation in Indonesia, but it does not rule out cases related to LGBT acts that ultimately demand settlement through legal channels. Likewise, within the military sphere, LGBT acts in Indonesian legislation have not been specifically regulated so that elements that can be imposed as a criminal act cannot be subject to a criminal act itself (LGBT acts singly).